Terrestrial planarians (Platyhelminthes, with three new species) and nemertines of Bermuda - Jones, Hugh D.; Sterrer, Wolfgang (Zootaxa, 2005)
Records of terrestrial planarians and nemertines found on Bermuda are summarized. Three new species of terrestrial planarian are described though they certainly originated elsewhere. These are Amaga expatria n. sp., Gigantea gouvernoni n. sp. (both Geoplanidae and originating from South or Central America) and Bipalium vagum n. sp. (Bipaliidae, probably originating from Asia). Records of other planarians (Bipalium kewense, Anisorhynchodemus sp., Dolichoplana striata and Rhynchodemus sylvaticus) as well as nemertines (Pantinonemertes agricola and Geonemertes pelaensis) are discussed with regard to origin, distribution and mode of dispersal.